2019
DOI: 10.1038/s41396-019-0486-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemosymbiotic bivalves contribute to the nitrogen budget of seagrass ecosystems

Abstract: In many seagrass sediments, lucinid bivalves and their sulfur-oxidizing symbionts are thought to underpin key ecosystem functions, but little is known about their role in nutrient cycles, particularly nitrogen. We used natural stable isotopes, elemental analyses, and stable isotope probing to study the ecological stoichiometry of a lucinid symbiosis in spring and fall. Chemoautotrophy appeared to dominate in fall, when chemoautotrophic carbon fixation rates were up to one order of magnitude higher as compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…If Loripes mucocytes effectively contribute to particle nutrition, that would suggest that the small adults in our study rely more on autotrophic nutrition and then shift to a higher amount of heterotrophic nutrition, as seen in larger adults, to sustain reproduction during spring. This hypothesis is in line with recent C and N stable isotope ratio findings on Loripes, which show an increasing level of autotrophy from April to October (Cardini et al 2019). These authors suggest that host nutrition relies on heterotrophy during spring and then turns mainly to chemoautotrophic nutrition during autumn.…”
Section: Sexually Determined Mucocytessupporting
confidence: 90%
See 2 more Smart Citations
“…If Loripes mucocytes effectively contribute to particle nutrition, that would suggest that the small adults in our study rely more on autotrophic nutrition and then shift to a higher amount of heterotrophic nutrition, as seen in larger adults, to sustain reproduction during spring. This hypothesis is in line with recent C and N stable isotope ratio findings on Loripes, which show an increasing level of autotrophy from April to October (Cardini et al 2019). These authors suggest that host nutrition relies on heterotrophy during spring and then turns mainly to chemoautotrophic nutrition during autumn.…”
Section: Sexually Determined Mucocytessupporting
confidence: 90%
“…Based on the previous arguments, we posit that mucocytes, given their correlation with water temperature and the size and reproductive status of the host, contribute to the host's heterotrophic nutrition, without ruling out a potential role in host immunity. Isotopic ratio and transcriptomic data (Carlier et al 2007;Cardini et al 2019;Yuen et al 2019) helped both to throw light on these findings and confirm them. The balance between bacteriocytes and mucocytes, varying seasonally to sustain reproduction, give histological support for the well-known mixotrophic status of Loripes, which shifts from autotrophy to heterotrophy.…”
Section: Sexually Determined Mucocytesmentioning
confidence: 82%
See 1 more Smart Citation
“…The biochemical mechanisms that promote such DON release should be addressed in future studies. Furthermore, it has rarely been questioned whether NH 4 + excretion by animals is solely a physiological process or if it might also be attributed to invertebrate-bacteria associations 70 . For example, Samuiloviene et al 38 found active transcription of nrfA gene (encoding for DNRA) in tube dwelling chironomid larvae, suggesting the presence of active ammonifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Although nitrogen in the form of nitrate and ammonium can be relatively abundant at the hydrothermal vents where chemosynthetic symbioses were first discovered and studied, it was unclear whether this could sustain the nitrogen requirements for these fast-growing chemosynthesisbased ecosystems. To build biomass, approximately one mole of nitrogen is required for every four to six moles of carbon (50,51). Considering that the symbionts are fixing enough carbon to sustain both themselves and their hosts, some of which grow to two meters in height, their nitrogen requirement must also be vastly higher than for chemolithoautotrophs thriving alone in vent environments.…”
Section: Context Of the Discovery Of Nitrogen-fixing Chemosynthetic Smentioning
confidence: 99%